2020
DOI: 10.4102/sajhivmed.v21i1.1107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adherence in virally suppressed and unsuppressed human immunodeficiency virus-positive urban patients on second-line antiretroviral treatment

Abstract: Background: Understanding antiretroviral therapy (ART) adherence may assist in designing effective support interventions.Objectives: This study elicited perspectives on how to promote treatment adherence from virologically suppressed and unsuppressed patients receiving second-line ART.Methods: This was a cross-sectional study conducted with randomly selected patients active on second-line ART, from five public health facilities in the Johannesburg inner city. Data were collected on demographics, clinical infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The trust and communication between patients on ART and treatment supporters is essential in improving and maintaining optimal adherence to treatment [ 25 ]. Some studies have reported treatment support as a predictor of adherence [ 38 , 70 ]. In this study, the interpersonal level factors consisting of relationships between patients and family members, friends, intimate partner(s) and healthcare providers will be discussed against previous studies to provide guidance on the role of treatment supporters in strengthening treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trust and communication between patients on ART and treatment supporters is essential in improving and maintaining optimal adherence to treatment [ 25 ]. Some studies have reported treatment support as a predictor of adherence [ 38 , 70 ]. In this study, the interpersonal level factors consisting of relationships between patients and family members, friends, intimate partner(s) and healthcare providers will be discussed against previous studies to provide guidance on the role of treatment supporters in strengthening treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa specifically, there is lack of reported knowledge about the effectiveness and impact of strategies currently employed to promote adherence in people living with HIV (PLHIV) who are taking ART (particularly young patients, males, and those experiencing severe treatment related side effects) [ 37 , 38 ]. Unfortunately, there are no quantitative studies of combination ART in South Africa (and even sub-Saharan Africa more generally) that have used a social-ecological perspective or approach.…”
Section: Introductionmentioning
confidence: 99%
“…With an earlier diagnosis, individuals are empowered to identify and modify their high-risk behaviors, potentially reducing the number of new HIV infections. This empowerment of consumers is not just limited to modifying lifestyle decisions but also involves being proactive in their health care decisions, which include adherence to clinic appointments and HIV treatment adherence (crucial to the prevention of viral rebound, treatment resistance, and the success of HIV management programs) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trust and communication between patients on ART and treatment supporters is essential in improving and maintaining optimal adherence to treatment (24). Some studies have reported treatment support as a predictor of adherence (37,56). In this study, the interpersonal level factors consisting of relationships between patients and family members, friends, intimate partner(s) and healthcare providers will be discussed against previous studies to provide guidance on the role of treatment supporters in strengthening treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…This lends to the lack of understanding of the interplay between the various factors involved at different levels of the treatment taking behaviour of the ART patient. In South Africa specifically, there is lack of knowledge about the effectiveness of adherence strategies currently employed to promote adherence in healthcare recipients (particularly young patients, males, and those experiencing severe treatment related side effects) and the impact thereof (36,37). Unfortunately, most adherence studies are not guided by any conceptual framework and subsequently are unable to draw adherence strategies from conceptual frameworks of any kind.…”
Section: Introductionmentioning
confidence: 99%